PENGARUH LITERASI MEDIA ISLAMI TERHADAP TINGKAT KESADARAN IFFAH SANTRI DI SEKOLAH ISLAM PERMATA SUNNAH PAKET B - Nining; Astutik, Anita Puji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital media has increased students' exposure to various online contents that are not always aligned with Islamic values. This situation may affect iffah awareness, defined as the ability to preserve personal dignity, modesty, and self-restraint in accordance with Islamic teachings. Therefore, this study aimed to examine the effect of Islamic media literacy on students' iffah awareness. This study employed a quantitative approach using a quasi-experimental one-group pretest-posttest design. The participants consisted of 54 students from Sekolah Islam Permata Sunnah Paket B selected through total sampling. Data were collected using a four-point Likert-scale questionnaire that had met validity and reliability requirements. The data were analyzed using the Kolmogorov–Smirnov normality test, the Wilcoxon Signed-Rank Test, and Normalized Gain (N-Gain) analysis. The findings revealed a statistically significant difference between the pretest and posttest scores (p = 0.001, p < 0.05). Furthermore, the average N-Gain score was 0.30, indicating a moderate improvement in students' iffah awareness following the implementation of the Islamic Media Literacy program. These findings suggest that Islamic media literacy has a positive effect on improving students' iffah awareness and may serve as an effective character education strategy for Islamic boarding schools in responding to the challenges of the digital media era.